Chapter L'azione educativa dell'ANPI per la formazione dei cittadini dentro e fuori la scuola - Pagliarulo, Gianfranco (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper highlights some of the initiatives the ANPI carried on in schools for spreading knowoledge about the Resistance movement. The contribution shows the objectives that guide ANPI and its action.